A Model of Inclusive Education Curriculum in Islamic Education Institutions: A Case Study in Banten Province, Indonesia - Ilyas, Elis Lisyawati; Setyaningrum, Nur; Sumarni, Sumarni (Jurnal Pendidikan Agama Islam, 2022)
Purpose – The objective of this study was to describe and analyze the inclusive education curriculum model according to the Decree of the Director General of Education in 2016. Design/methods/approach – Qualitative descriptive methods in this study were used to describe the use of the inclusive curriculum model thoroughly and empirically in Islamic schools (Madrasah). In-depth interviews, observation, and document studies are used to collect field data using triangulation to conclude. Findings – Based on the field data results, the development of the curriculum for the four Madrasahs which were the target of research adapted more show duplication by modifying some of its elements/items/components. No fully modified curriculum components were found but only learning strategies or approaches based on the needs and conditions of students with special needs. This has an impact on the potential development of children with special needs who are not yet optimal. Research implications/limitations – This research was conducted in 4 Madrasah in Banten Province. There are 18 Madrasah in other provinces which have become pilot projects for inclusive education. Originality/value – The maximum development of a student’s potential can be made possible by various other development models, such as modification, substitution, and omission.